Mitigation Options of Carbon Footprint for Chinese Dairy Farms: Feasibility Inventory - Hongmin Dong; Sha Wei; Yue Li; Zhiping Zhu (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The challenge of Chinese dairy sector is creating a low greenhouse gas emission chain. Institute of Environment and Sustainable Development in Agriculture, Chinese Academy of Agricultural Sciences and College of Animal Science and Technology, China Agricultural University have taken on in their joint effort to support the China dairy sector. This brochure aims to help those involved to find their way towards more effective and productive for sustainability. All stakeholders, including dairy farmers, milk processors, diary associations, government- need to work together if we are to achieve more sustainable dairy chain. We have explored the tools that can be used to get all stakeholders in the dairy chain closer to their sustainability goals. In this brochure you will find best mitigation options for a low emission dairy chain. The feasible inventory for different regions and farm scale of China can also be found in this brochure. This mitigation options inventory can also be used in other livestock sectors.